FAKTOR-FAKTOR YANG MEMPENGARUHI EARNINGS MANAGEMENT PADA PERUSAHAAN SEKTOR INDUSTRI DI BEI - Suryata, Fedella Stephanie; Bangun, Nurainun (Fakultas Ekonomi, Universitas Tarumanagara, 2025)
This study was conducted to analyze the effect of good corporate governance, financial performance, and capital structure on earnings management in miscellaneous industry, consumer goods industry, and basic industry and chemical sector companies listed on the Indonesia Stock Exchange for the 2019-2021 period. The technique used in this study to determine the research sample was purposive sampling. The number of research samples is 76 companies from 217 companies registered. This study uses a quantitative approach. The data analysis method used is multiple linear regression analysis what helped by Eviews version 12 program and Microsoft Excel 2013. The results showed that simultaneously good corporate governance, financial performance, and capital structure have a significant effect on earnings management. While the results of partial research show that board size and capital structure have a negative and insignificant effect on earnings management. Board independence has an insignificant effect on earnings management. Financial performance has a positive and significant effect on earnings management.